Characteristics and differences in the verbal responses of expert and novice basketball coaches elicited by cognition of fixed vtr images and vr images - Yasuyuki, N. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In this study, in order to examine how coaches perceive phenomena during a basketball game, we reproduced fixed VTR images that captured the entire space where the phenomena occurred and VR images recorded with a 360-degree omnidirectional camera, and explored the differences in the coaches` verbal responses during viewing of each type of image. METHODS: The persons to be analyzed are 2 novice coaches and 2 proficient coaches in the college basketball club. As for the image collection method, the practice games of the college basketball were recorded by installing a fixed video camera and a 360-degree omnidirectional camera on the side of the benches where the coaches sit. 4 subjects uttered while watching the images recorded by a fixed video camera (hereinafter referred to as "fixed VTR images") and the images recorded by a 360-degree omnidirectional camera (hereinafter referred to as "VR images"). The subjects freely utter what they think while watching the recorded game images. RESULTS: As a result of classifying utterances, there were 9 categories. The categories are situation description, expectations and proposals, prediction, retrospection, praise (general), praise (concrete), instruction, and criticism. The fixed VTR images were able to elicit a certain amount of verbal responses from the novice coaches in categories that objectively captured the phenomena taking place, such as situation description, prediction, and general praise or criticism. Among the proficient coaches, the same verbal responses were elicited during fixed VTR image viewing as during VR image viewing, regardless of category. While viewing the VR images, the novice coaches tended to make fewer verbal responses in all categories, whereas the proficient coaches made similar verbal responses in all categories as they did while viewing the fixed VTR images. In addition, more verbal responses of the expectations and suggestions, praise, and instructions categories were made by the proficient coaches during VR image viewing than during fixed VTR image viewing. CONCLUSION: 1) From fixed VTR images, both novice and proficient coaches tended to observe phenomena objectively, in terms of being able to describe the situation and offer guidance and criticism. 2) From VR images, proficient coaches tended to offer praise or instructions on the basis of specific individual characteristics of player or team movements.